2021
DOI: 10.1177/10778012211019044
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Anxiety on the Risk of Sexual Victimization via Assertiveness in an Ethnically Diverse Sample

Abstract: Preliminary evidence suggests social anxiety may increase the risk of sexual victimization via decreased sexual assertiveness. A sample of 2,043 undergraduate students completed an online survey. Analyses of moderated indirect effects examined whether gender or ethnicity moderated the indirect effect of social anxiety on sexual victimization via sexual assertiveness. No moderation effects were found, but the indirect effect of social anxiety on sexual victimization via sexual assertiveness was significant for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…We observed that people who reported non-consensual TMSI experiences (including feeling pressured, coerced, and receiving unwanted sexts) also reported increased anxiety symptoms. This finding may translate to social anxiety; some research suggests that people higher in social anxiety are at greater risk of non-consensual sexual experiences overall [ 84 ]. We also found preliminary evidence that some forms of TMSI (i.e., sexting) predicted later increased reports of anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that people who reported non-consensual TMSI experiences (including feeling pressured, coerced, and receiving unwanted sexts) also reported increased anxiety symptoms. This finding may translate to social anxiety; some research suggests that people higher in social anxiety are at greater risk of non-consensual sexual experiences overall [ 84 ]. We also found preliminary evidence that some forms of TMSI (i.e., sexting) predicted later increased reports of anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%